ANALYSIS OF PROFITABILITY AND LIQUIDIA RATIO IN MEASURING FINANCIAL PERFORMANCE IN PHARMACEUTICAL COMPANIES LISTED ON THE IDX IN 2018-2021 - Friska Valentine Kaunang; Judith Tagal Gallena Sinaga (SEAN Institute, 2023)
This study aims to analyze the profitability and liquidity ratios in measuring the financial performance of pharmaceutical companies in Indonesia, which are listed on the stock exchange. The approach in this research is quantitative. The data analysis technique in this study was descriptive. That is, the data was obtained and processed in such a way as to provide systematic and accurate data regarding the problems studied. The secondary data sources that the authors use come from pharmaceutical sector companies in the form of financial reports for four years. Based on the results of this study, it can be seen that the profitability ratios of the pharmaceutical sector, as measured using NPM, ROA, and ROE, have fluctuated. That shows the company's ability to profit from managing company assets, equity, and revenues. The results show that the profitability and liquidity ratios significantly affect the financial performance of pharmaceutical companies in Indonesia